Avaliação de cereais de estação fria de duplo-propósito em pastejo com bovinos leiteiros - Meinerz, Gilmar Roberto (2012)
This research was conducted with the objective to evaluate alternatives of utilization of cool season pastures, under grazing with dairy cattle. Two main experiments were conducted. On the first was evaluated the use of Agro Zebu black oat, UPF 18 white oat, BRS Serrano rye and BRS Tarumã wheat, submitted to double purpose management (forage and grains).On the second was evaluated black oat, ryegrass and wheat exclusively on grazing, in which was also evaluated the ingestive behavior of lactating cows and the production of conserved forage from pasture remaining biomass. The grazing method was the rotative stocking, with a day of occupation. Early growth, herbage and leaf blades biomass production, grains, botanical and structural compositions, the period of use and nutritional value, beyond the stocking rate and herbage intake were evaluated. The behavioral variables studied were grazing, rumination and idleness time, bite rate, number, interval and duration of meals. From conserved forage were evaluated yield, the fermentative parameters of silage and nutritive value of silage and hay. The experimental design was completely randomized with three replications and repeated measures, except the ingestive behavior, which was designed in randomized complete blocks and conserved forage, who present a 3 x 2 factorial scheme. In the double purpose experiment, white oat was the pasture with most early growth. Wheat present higher forage production, leaf blades biomass, grain yield, hectoliter weight and nutritional value were similar between genotypes. In the experiment on pasture, ryegrass and wheat presented higher herbage and leaf blades biomass yields and supported higher stocking rates. On the pastures high nutritional value was verified, with higher values of crude protein and digestibility of neutral detergent fiber for black oat and wheat. Grazing and rumination time was higher for black oat, in which there was a greater bite rate, caused by reduced leaf blades allowance. At ryegrass and wheat pastures, cows had shorter meals and in great numbers throughout the day. For silage, was verified appropriate fermentation parameters and lower losses of soluble components, providing forage with a higher nutritional value in compared to hay. The results show that wheat is most appropriate for the double purpose management and has similar performance to ryegrass under grazing and animal ingestive behavior. For the remaining biomass of cool season pastures, the conditions for conservation as silage and hay were satisfactory.